The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/mc.22526
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cell mediated acquired chemoresistance in head and neck cancer can be abrogated by aldehyde dehydrogenase 1 A1 inhibition

Abstract: Chemoresistance leading to disease relapse is one of the major challenges to improve outcome in head and neck cancers. Cancer Stem Cells (CSCs) are increasingly being implicated in chemotherapy resistance, this study investigates the correlation between CSC behavior and acquired drug resistance in in vitro cell line models. Cell lines resistant to Cisplatin (Cal‐27 CisR, Hep‐2 CisR) and 5FU (Cal‐27 5FUR) with high Resistance Indices (RI) were generated (RI ≥ 3) by short‐term treatment of head and neck squamous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…ALDH1-positive CSC-like cells were enriched in ovarian tumors following the taxane/platinum-based therapy 18 . In line with these, ALDH1 inhibition reduced chemoresistance in head and neck cancer, and effectively blocked the proliferation and survival in ovarian cancer spheroids 19,20 . In drug-resistant ovarian cancer cell lines, high expression of BCRP and multidrug resistance protein 1 (MDR1) was accompanied by ALDH1A1 overexpression, and the inhibition of ALDH activity reduced drug efflux transporter expression, leading to sensitization to chemotherapy 21 .…”
Section: Introductionsupporting
confidence: 58%
“…ALDH1-positive CSC-like cells were enriched in ovarian tumors following the taxane/platinum-based therapy 18 . In line with these, ALDH1 inhibition reduced chemoresistance in head and neck cancer, and effectively blocked the proliferation and survival in ovarian cancer spheroids 19,20 . In drug-resistant ovarian cancer cell lines, high expression of BCRP and multidrug resistance protein 1 (MDR1) was accompanied by ALDH1A1 overexpression, and the inhibition of ALDH activity reduced drug efflux transporter expression, leading to sensitization to chemotherapy 21 .…”
Section: Introductionsupporting
confidence: 58%
“…Accumulating evidence has showed that chemotherapy failure might be blamed for the existence of CSCs, 24, 25, 26, 27 and we speculated that CTGF may mediate TMZ resistance through stem-like properties acquisition. To examine this notion, we evaluated the stem-like properties expression in CTGF overexpressed or knockdown GB cells.…”
Section: Resultsmentioning
confidence: 91%
“…NCT-501, which harbors a scaffold derived from caffeine, is a selective ALDH1 inhibitor. [66] It has been shown to be effective against patient-derived head and neck cancer cells, [67] where other conventional molecules were proven to be ineffective. The heterogeneous cell lines used in these studies had elevated levels of CD44, CD133 and ALDH1, indicating an increased CSC population in these tumors, which helps rationalize the susceptibility of these cells to NCT-501 treatment.…”
Section: Targeting the Metabolic State Of Cscs: Mitochondrial Metabolmentioning
confidence: 99%